2013
DOI: 10.1007/s00213-013-3371-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphodiesterase 10A has differential effects on dopamine D1 and D2 receptor modulation of sensorimotor gating

Abstract: Rationale Inhibitors of phosphodiesterase 10A (PDE10A), an enzyme highly expressed in medium spiny neurons of the mammalian striatum, enhance activity in direct, dopamine D1 receptor-expressing and indirect, D2 receptor-expressing striatal output pathways. The ability of such agents to act to potentiate D1 receptor signaling while inhibiting D2 receptor signaling suggest that PDE10A inhibitors may have a unique antipsychotic-like behavioral profile differentiated from the D2 receptor antagonist-specific antips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…In the striatum, PDE10A is largely distributed in medium spiny neurons, which are the striatal projection units and 95% of striatal neurons. This vast distribution pattern indicates that PDE10A inhibitors influence both striatal output pathways and globally the BG circuitry (Gresack et al, 2014; Megens et al, 2014; Strick et al, 2010), which is consistent with their predicted antipsychotic efficacy (Carlsson, 2001; Goff and Coyle, 2001; O’Donnell and Grace, 1998). Moreover, the analysis of single circuit activation has recently demonstrated that both direct and indirect striatal output pathways act in coordinated motion, highlighting the notion that these two information streams function cooperatively rather than competitively (Cui et al, 2013).…”
Section: Discussionsupporting
confidence: 65%
“…In the striatum, PDE10A is largely distributed in medium spiny neurons, which are the striatal projection units and 95% of striatal neurons. This vast distribution pattern indicates that PDE10A inhibitors influence both striatal output pathways and globally the BG circuitry (Gresack et al, 2014; Megens et al, 2014; Strick et al, 2010), which is consistent with their predicted antipsychotic efficacy (Carlsson, 2001; Goff and Coyle, 2001; O’Donnell and Grace, 1998). Moreover, the analysis of single circuit activation has recently demonstrated that both direct and indirect striatal output pathways act in coordinated motion, highlighting the notion that these two information streams function cooperatively rather than competitively (Cui et al, 2013).…”
Section: Discussionsupporting
confidence: 65%
“…In line with these findings, Sotty et al (2009) proposed that PDE10A inhibition may favor D2 MSNs at basal dopaminergic conditions and prefer D1 MSNs under an elevated dopaminergic state (Sotty et al, 2009). Furthermore, Gresack et al (2014) demonstrated with a rodent model of sensorimotor gating that the relative dopaminergic tone at D1 and D2 receptors impacts the level to which PDE10A inhibitors can activate the direct pathway (Gresack et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Both direct and indirect pathways have competing effects on antipsychotic‐like activities and motor functions in rodents . Compared to other PDE10A inhibitors, the balanced activation of the direct and indirect pathway MSNs by TAK‐063 may represent a novel therapeutic approach to treat patients with schizophrenia, either alone or in combination with other D 2 antagonist antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other PDE10A inhibitors such as MP‐10 and compound 1 [1‐[cyclopropylmethyl]‐4‐fluoro‐5‐[5‐methoxy‐4‐oxo‐3‐(1‐phenyl‐1H‐pyrazol‐5‐yl)pyridazin‐1(4H)‐yl]‐3,3‐dimethyl‐1,3‐dihydro‐2H‐indol‐2‐one] (previously synthesized by Takeda Pharmaceutical Limited, TAK‐063 showed comparable activation of indirect pathway MSNs while producing partial activation of direct pathway MSNs by its fast dissociation property in the rat striatum . These MSN pathways have competing effects on antipsychotic‐like activities and motor functions in rodents . TAK‐063 with this unique activation pattern of MSN pathways produces antipsychotic‐like effects in the multiple paradigms of rodent models .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation